Relativistic corrections to the ground-state energy of the positronium molecule - Bubin, Sergiy; Stanke, Monika; Ke¸dziera, Dariusz; Adamowicz, Ludwik (My University, 2007)
The leading-order relativistic corrections to the ground-state energy of the positronium molecule Ps2 have been computed within the framework of perturbation theory. As the zero-order wave function we used a highly accurate nonrelativistic variational expansion in terms of 6000 explicitly correlated Gaussians that yielded the lowest variational upper bound for this system to date. We also report some expectation values representing the properties of Ps2
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; positronium molecule